Pengaruh Konservatisme Akuntansi dan Tata Kelola Perusahaan yang Baik terhadap Manajemen Laba pada Perusahaan Badan Usaha Milik Negara - Anjarningsih, Tita; Suparlinah, Irianing; Ayu Sri Wulandari, Ratu; Hidayat, Taufik (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study was conducted to find confidence about the factors that affect earnings management in SOEs in 2018-2019 through accounting conservatism, audit committee expertise, independence commissioners. Research methodology: The methods in this research were quantitative with sample of 60 SOEs, sourced secondary data from annual reports and uses the EViews-9 application. Results: The conclusions are Random Effect selected as the model: (1) Earnings management significantly influenced by accounting conservatism in a positive direction, (2) Earnings management not significantly influenced by audit committee expertise, (3) Earnings management not significantly influenced by the independence commissioners. Limitation: In this study only the three variables and the period 2018-2019. Contribution: If the company applies accounting conservatism, it must be applied wisely and consistently, because will effect increase to income decreasing or smoothing. Likewise, empowerment of expert audit committee and independent commissioner needs to be done properly to balance the use of flexibility in accounting standards with the avaibility of quality financial reports. Because, in SOEs, even they have implemented GCG, they have not been able to reduce the opportunistic earnings management.